Active Movement in Elementary School: Stimulating Basic Movement Skills for Lower Grade Students - Husein Allsabah, M. Akbar; Sugito; Prasetya Kurniawan, Wing; Putra, Rendhitya Prima; Junaidi, Slamet; Shandy, Dwi Kurnia; Tri Nugroho, Ferdian (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Basic motor skills are essential for the physical, cognitive, and social development of elementary school children, especially in the early grades (grades 1–3). However, these skills often do not receive sufficient attention in education. This community service initiative aims to improve students' basic motor skills through engaging educational games, while also improving teacher competence and encouraging parental participation. The program was implemented at Ngeronggo 2 Kediri city elementary school, involving 45 students, 8 teachers, and 45 parents. The methods used included training for teachers and parents, play activities for children, and assessment through observation, student reflection, and surveys. The results showed that 87% of students reported enjoying participating in the activities, while 89% were actively involved in all movement activities. Teachers' average knowledge scores increased from 63.75 to 87.5 after the training. Additionally, 89% of parents reported benefits from the Daily Movement Calendar, while 82% said their children were interested in playing the games again at home. These findings indicate that instructional games effectively improve children's basic motor skills and receive positive support from educators and families. This approach is relevant for implementation in other elementary schools to foster a culture of active and healthy movement from an early age.